THE IMPACT OF MANAGING THE CULTURAL HERITAGE OF PURA PUSEH BATUAN AS A TOURIST ATTRACTION ON THE BATUAN VILLAGE COMMUNITY - Praptiningsih; Anak Agung Istri Wahyu Bira Dewi; I Putu Agus Pramartha Wijaya (Ride: Journal of Cultural Tourism and Religious Studies, 2025)
Pura Puseh Batuan is a tourist attraction (DTW) that contains a National Cultural Heritage site. The Cultural Heritage of Pura Puseh Batuan is visited by both domestic and international tourists due to its architectural beauty, historical heritage, and the cultural aspects present in the community of Batuan Village. As a tourist attraction managed by the community through Batuan Customary Village, this research focuses on the impact of its management on the Batuan Customary Village community. This is a qualitative research, and data for this study were collected through observation, interviews, and literature review. Informants were selected using purposive sampling technique. The research results indicate that the management of the Cultural Heritage of Pura Puseh Batuan as a tourist attraction has a positive impact on the Batuan Village community, particularly in terms of the economy, as it can improve the livelihood of the local residents. Although the local community interacts directly with tourists, it does not have a negative influence on the preservation of the cultural values held by the Batuan Village community, as the local people highly value their cultural heritage